Performance of Wanggu Watershed Management Based on Land Indicators - Kahirun; Hamzah, Nurnaningsih; Rahman, Arwan A.; Yusria, Wa Ode; Hajar, Nurhayati; Putra, Erich Nov (Indonesian Journal of Environmental Management and Sustainability, 2023)
Based on the study, it was found that the land in the Wanggu Watershed is highly dynamic due to community activities such as agriculture, plantations, forestry, and settlement development. This can affect the performance and carrying capacity of the land in the watershed. The purpose of study was to evaluate the performance of watershed management and analyze the land-carrying capacity based on indicators of land. The parameters analyzed were the percentage of critical land area, the percentage of vegetation cover, and the erosion index. To obtain the data needed for the study, both primary and secondary data were used. Primary data was obtained through the overlay of the base map to obtain a map of critical land, making land cover maps, and calculating erosion prediction and carrying capacity analysis of the Wanggu Watershed. Secondary data was obtained from related agencies in the form of critical land data, land cover data, literature, policy documents, and study reports that are relevant to watershed management performance. The results of the study showed that the percentage of critical and somewhat critical land area in the Wanggu Watershed is 16.07 percent, which means that this value still qualifies as high category critical land recovery. The percentage of vegetation cover, especially forest cover, is 27.10 percent, which is still in bad condition. The average erosion index value is 2.00, which is high. Based on these three parameters of land condition indicators in the Wanggu Watershed, the performance of watershed management has a poor land carrying capacity category with a value of 50. Overall, the study highlights the need for better management and conservation of the land in the Wanggu Watershed to improve its performance and carrying capacity.